Revisión de literatura sobre la gestión de calidad en la industria farmacéutica (2021)
The objective of this article is to carry out a bibliographic review on quality management in the pharmaceutical industry, which allows us to know its importance in organizational performance, in addition to describing its interaction with quality costs. Additionally, an international perspective of the issue is presented, describing case studies that show the impact generated by quality management in the pharmaceutical sector. For the above, a descriptive qualitative study is carried out, developed under documentary research, searching for articles in English and Spanish in different databases such as Sciencedirect, Emerald and Scopus. The results obtained show that within the pharmaceutical industry a balance is sought between the quality of the pharmaceutical product and issues related to marketing and sales. To achieve this balance, quality management is necessary, since it allows to analyze and determine on time what are the failures of the process, and take corrective and preventive measures that will be reflected in the balance sheets of an organization.